A critical review on resource allocation mechanisms in grid computing - Dakkak, Omar; Awang Nor, Shahrudin; Che Mohamed Arif, Ahmad Suki (2015)
t- In recent years, the fast evolution in the industry of computer hardware such as the processors, has led the application developers to design advanced softwares that require massive computational power.Thus, Grid Computing has emerged in order to handle the computational power demands that requested from the application.To manage the scheduling of resources and arranging the jobs based on certain criteria, resource allocation mechanisms are used.In this paper, we critically review some of these mechanisms in “Grid Computing” environment.In addition, the paper offers a comparison among the reviewed mechanisms in order to guide the researcher in choosing the suitable mechanism that fits the running application